METODE KOMUNIKASI DAKWAH PROF. DR. H. M. RASJIDI TENTANG ALIRAN KEBATINAN DALAM BUKU ISLAM DAN KEBATINAN KARYA H. M. RASJIDI - Fajar Ramadianto; Miswanti (JOISCOM (Journal of Islamic Communication), 2024)
ABSTRACT In Indonesia at this time the majority of people adhere to Islam, but so there are still many who have not implemented Islamic religious teachings in accordance with the Shari'ah according to the Koran and Hadith, both those who live in rural areas and in urban areas, especially the common people. The purpose of this study is to find out how the da'wah communication method carried out by Prof. Dr. H M Rasjidi regarding the mysticism in the book Islam and Kebatinan. This research is library research with data collection techniques using primary data and secondary data, by documenting or collecting data from documents in the form of books, magazines, journals, websites and others. The data source for this research is a book written by Prof Dr H M Rasjidi entitled "Islam and mysticism" and also from supporting data obtained from libraries, journals and websites. Based on the results of research by the author that the communication method used by Prof. Dr. H M Rasjidi regarding mysticism is the mujilah method. With this method, everyone who reads the book written by Prof. Dr. H M Rasjidi knows clearly the difference between mysticism and Islam Keywords: Mysticism, Da'wah Communication Methods